Pico and Its Implementation in Medical Libraries With Special Relevance to Government Medical College Kota (LIS TODAY, 2023)
The aim of this research is to see the PICO and its implication for the medical library with  special reference to Government Medical College Kota. A medical library is a kind of library  purposely designed to assist medical doctors, physicians, and other related medical practitioners,  who practice medicine whose concerned with promoting and maintaining health through the  diagnosis study, of a recipient of health care service performed by a healthcare professional, PICO is  the process of finding the appropriate response to the debt that arises in patient care depends on how  we structure the relevant of these methods. The author will look at its implication in medical libraries,  present, and future, Moreso, medical libraries will be vividly defined, and there used the PICO  framework patient or problem, intervention or issues, and the outcome will also further explain, the  challenges of the patient or problem, intervention or issues, and the outcome (PICO) in medical  libraries to the medical practitioner’s preferred solution to the medical practitioners.  Recommendation of the discussion and final conclusion of the study and reference.
Keywords: Patient; Intervention; Control; Outcome (PICO); Medical Libraries (ML); Government Medical College Kota (GMCK)